'Fragmentation or unity of public international law’ revisited: analysing the European Convention on Human Rights when the European Court takes cognisance of public international law norms - Rachovitsa, Adamantia (2013)
This thesis addresses the legal challenges arising in the context of the ‘fragmentation or unity of public international law’. The question of the so-called fragmentation of public international law mainly refers to the phenomenon of diversification and expansion of public international law. In recent years, the proliferation of international bodies entrusted with the task of monitoring States’ compliance with their international obligations has increased the possibility of conflicting interpretations of similar or identical rules of international law. In this context, it is claimed that international courts with limited ratione materiae and personae jurisdiction fragment international law and threaten its unity. This thesis examines the question of the fragmentation of public international law from the perspective of the European Court of Human Rights (ECtHR). In the view of the present author, the European Court has developed the autonomous interpretative principle of taking cognisance of public international law norms when interpreting the European Convention on Human Rights (ECHR). The ECtHR employs this interpretative principle in a fashion that is distinct from other seminal interpretative principles, namely the so-called comparative interpretation, the dynamic interpretation and the principle of effectiveness. Furthermore, this thesis provides in depth analysis of the ECtHR’s legal reasoning. It reaches conclusions on the type of public international law norms that the ECtHR takes into account and the conditions a norm must satisfy to qualify as ‘relevant’ and ‘applicable in the relations between the parties’. This thesis also provides an overall assessment of the different uses of public international law norms in the ECtHR’s reasoning, when expanding or restricting the scope of the rights and freedoms of the ECHR. It stresses the importance of the ECtHR’s practice of relying upon public international law norms in order to (re-)interpret the ECHR and overrule its previous case-law. Finally, this thesis explores the boundaries that should be set to restrict the impact of other relevant public international law norms on the construction of the ECHR. The study concludes that, in principle, the ECtHR does not threaten the unity of international law, but reads the ECHR harmoniously to public international law. The findings of this thesis also furnish evidence that the ECtHR has competence to pronounce on questions relating to international law and that, on certain occasions, it develops and enriches the scope and content of international law.